2009
DOI: 10.1172/jci35958
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen-induced hepatotoxicity in mice is dependent on Tlr9 and the Nalp3 inflammasome

Abstract: Hepatocyte death results in a sterile inflammatory response that amplifies the initial insult and increases overall tissue injury. One important example of this type of injury is acetaminophen-induced liver injury, in which the initial toxic injury is followed by innate immune activation. Using mice deficient in Tlr9 and the inflammasome components Nalp3 (NACHT, LRR, and pyrin domain-containing protein 3), ASC (apoptosis-associated specklike protein containing a CARD), and caspase-1, we have identified a nonre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
584
6
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(634 citation statements)
references
References 45 publications
35
584
6
9
Order By: Relevance
“…Previous reports have described apoptotic gDNA as the major activator of TLR9 in APAP-induced liver injury. 34 However, we and others 8 have provided evidence that mitDNA also plays a key role in immune system activation by TLR9 signaling during ALF.…”
Section: Discussionmentioning
confidence: 81%
“…Previous reports have described apoptotic gDNA as the major activator of TLR9 in APAP-induced liver injury. 34 However, we and others 8 have provided evidence that mitDNA also plays a key role in immune system activation by TLR9 signaling during ALF.…”
Section: Discussionmentioning
confidence: 81%
“…6 Recent studies have revealed the expression of inflammasomes in innate immune cells including monocytes, macrophages, neutrophils, and dendritic cells. Furthermore, non-immune cells including hepatocytes, [57][58][59] stellate cells, 60 endothelial cells, 61,62 and myofibroblasts 63 also contain the functionally active inflammasome complex. Studies at the mRNA levels support the expression of NLRP1, 2, 3, 6, 10, 12, and NLRC4 in the liver.…”
Section: Liver and The Inflammasomesmentioning
confidence: 99%
“…1 Interestingly, all studies that investigated a role of the Nalp3 inflammasome and interleukin-1b (IL-1b) in APAP hepatotoxicity are in agreement that damage-associated-molecular patterns released from necrotic cells activate macrophages to generate cytokines, including pro-IL-1b. 1,3,4 All groups also agree that inhibition or deficiency of caspase-1 eliminates processing of pro-IL-1b to the active cytokine. 1,3,4 Most important, all agree that only a few pg/mL of IL-1b are actually produced during APAP hepatotoxicity.…”
mentioning
confidence: 93%
“…1,3,4 Most important, all agree that only a few pg/mL of IL-1b are actually produced during APAP hepatotoxicity. 1,3,4 However, the fact that mice treated with 10,000-fold more recombinant IL-1b had no effect on APAPinduced liver injury clearly indicates that minor quantities of endogenously generated IL-1b have no impact on APAP hepatotoxicity. 4 …”
mentioning
confidence: 93%
See 1 more Smart Citation